Pengaruh E-LKPD berbasis Wizzer Me untuk Meningkatkan Hasil Belajar Siswa pada Materi Kekayaan Budaya Indonesia Kelas 4 SD Negeri 2 Ngrance - Imelda, Rizka; Putri, Dya Ayu Agustiana; Ana, Ria Fajrin Rizqy (Universitas Nusantara PGRI Kediri, 2025)
E-LKPD is a medium as well as teaching material in the learning process to improve student learning outcomes. Learning outcomes emerge when students are motivated in learning. The aim of the research is to determine the effect of interactive learning media on the learning outcomes of grade 4 students at SD Negeri 2 Ngrance. This research is quantitative with an experimental type. The sampling technique used saturated sampling with 30 respondents. Data collection techniques use learning outcomes tests. The data analysis technique uses the t test (Independent Samples T-Test) in Jamovi 2.3.28. The results of the post-test t test showed that the p-value was <0.001, then the p-value was <0.05 and H0 was rejected and Ha was accepted, which means that the Wizzer.me-based E-LKPD had a positive influence on student learning outcomes on Indonesian natural wealth material. Based on the results of the hypothesis, it was found that there was a significant influence on Wizzer.me-based E-LKPD to improve the learning outcomes of grade 4 students at SD Negeri 2 Ngrance.